BIM-based methodology for the seismic performance assessment of existing buildings - Lopes, Gonçalo Correia (2020)
This presents a BIM-based methodology for the seismic performance assessment of existing mixed URM-RC buildings that consists of four phases: (1) Anamnesis, dedicated to the survey and collection of facts about the existing building, the structure and its environs. It aims at a better understanding of the complexity of different layers, historic phases, interventions and additions; (2) Diagnosis, dedicated to the analysis and interpretation of the collected facts in order to obtain the necessary understanding of the current state of conservation, the building’s behaviour and performance, and to discern about the eventual need for intervention; (3) Therapy, corresponding to the actual retrofitting design and can be performed using a fully developed information model (as in the case of new design), along with advanced BIM-based analysis and simulation methods to predict the expected improved performance and the related life cycle costs from the application of the proposed retrofitting measures and to evaluate different retrofitting proposals; and (4) Control, entailing a series of cyclical and regular monitoring actions and the implementation of strategies for a preventive conservation plan.